A quantitative and qualitative assessment of the utilization of mobile computing devices by clinical pharmacists. Issue 3 (September 2016) - Dahri, Karen; Gong, Yin; Loewen, Peter
Abstract: Objective: The primary objective of this study was to characterize mobile computing device (MCD) usage by clinical pharmacists who provide direct patient care in an institutional setting. The secondary objective was to gain insight into pharmacists' decision-making processes for choosing applications to use in practice. Methods: A cross-sectional survey and focus group-based study was conducted at a large multi-site health authority. Descriptive statistics were used to analyze the survey responses with between-group comparisons being made as appropriate. A mixed-methods approach was used to analyze the quantitative and qualitative data obtained in this study. Results: One hundred and thirty-six pharmacists responded to the survey with eighty-nine (65%) reporting that they used a MCD at work. Devices were most frequently used to access point of care references (97%) and online search engines such as Google or Wikipedia (90%). Participants most often used between 1 and 5 mobile and website based applications for 30–60 min each day to support clinical decision-making. Increased efficiency, trust in their institutional review process, and the reputation of the app developers were the main influences on which apps pharmacists chose to use in practice. Conclusions: While the pharmacists studied were making daily use of their own MCDs, they were used for a limited range of functions. Using apps that are decision support tools, especially those with integrated patient specific information, may assist pharmacists in making health care decisions and could further enhance the care they provide. Highlights: Pharmacists used their own MCD for work when their institution did not provide one. MCDs were mostly used for accessing point-of-care references and search engines. Efficiency, reputation and institutional endorsement drove app selection.